ANALISIS PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUASAN KONSUMEN PADA TOKO BARU MOTOR SPORT (BMS) SAMARINDA - Agus Trisihnyo (Universitas Muhammadiyah Kalimantan Timur, 2018)
Changes that occur in the business world today is completely uncertain. For that every company that wants to win the competition and success in this century must apply the concept of product differentiation then the company can use all the resources and advantages that exist in exploiting all changes to win the competition. Differentiation is very important and suitable as the key to success in the company, then this study was conducted with the aim to determine the effect of product differentiation on customer satisfaction at New Store Motor Sport (BMS) Samarinda. Companies in running their business must apply differentiation, where differentiation is one type of competitive advantage that can be owned by the company. Because of the suspected application of product differentiation is very influential on customer satisfaction of a company. This research was conducted by conducting research on product differentiation policy at New Store Motor Sport (BMS) Samarinda. The method used is simple regression method and correlation coefficient and t test to see the influence and relationship of product differentiation to customer satisfaction. The results showed that product differentiation has a strong relationship to customer satisfaction in New Store Motor Sport (BMS) Samarinda. This is evidenced from the results obtained in testing the hypothesis where the value of t count = 13.29> from ttable = 1.701 at  = 0.05 or 5% and the correlation coefficient of 0.929 and the value of coefficient of determination = 86.3%, then the regression equation simple obtained is y = 7.707 + 0.87106 x. It means that every decrease of product differentiation as 1% in New Store Motor Sport (BMS) Samarinda will increase consumer satisfaction equal to 0,87106%. It was concluded that the key to success of New Motor Sport Stores (BMS) of Samarinda in reaching and serving the market should apply the concept of product differentiation that can increase customer satisfaction and continue to be a successful company and can win the competition.